Research on aerodynamics of a wing-in-surface-effect ship by theory and experiment - Tang, Pham Xuan; Thang, Ngo Tri; Uy, Pham Vu; Hai, Duong Ngoc (Vietnam Journal of Mechanics, 2007)
The paper presents the results of theoretical and experimental studies of the aerodynamic characteristics of a wing-in-surface-effect ship (WISES), which was made under coordination of the Institute of Mechanics, Vietnamese Academy of Science and Technology. The theoretical researches are carried out by the half analytical method and together by the linear and nonlinear vortex lattice methods. The experiment was conducted by the model on wind tunnel OTl of The Technical Institute of Air Force - Air Defense.